Enhancement of RNA-directed DNA methylation of a transgene by simultaneously downregulating a ROS1 ortholog using a virus vector in Nicotiana benthamiana - Otagaki, Shungo; Kasai, Megumi; Masuta, Chikara; Kanazawa, Akira (Frontiers in Genetics, 2013)
Cytosine methylation can be induced by double-stranded RNAs through the RNA-directed DNA methylation (RdDM) pathway. A DNA glycosylase REPRESSOR OF SILENCING 1 (ROS1) participates in DNA demethylation in Arabidopsis and may possibly counteract RdDM. Here, we isolated an orthologue of ROS1 (NbROS1) from Nicotiana benthamiana and examined the antagonistic activity of NbROS1 against virus-induced RdDM by simultaneously inducing RdDM and NbROS1 knockdown using a vector based on Cucumber mosaic virus. Plants were inoculated with a virus that contained a portion of the CaMV 35S promoter, which induced RdDM of the promoter integrated in the plant genome and transcriptional silencing of the green fluorescent protein gene driven by the promoter. Plants were also inoculated with a virus that contained a portion of NbROS1, which induced downregulation of NbROS1. Simultaneous induction of RdDM and NbROS1 knockdown resulted in an increase in the level of cytosine methylation of the target promoter. These results provide evidence for the presence of antagonistic activity of NbROS1 against virus-induced RdDM and suggest that the simultaneous induction of promoter-targeting RdDM and NbROS1 knockdown by a virus vector is useful as a tool to enhance targeted DNA methylation.